Experimental measurements and modelling of vapour−liquid equilibria for four mixtures of 2, 3, 3, 3−tetrafluoropropene (R1234yf) with 1, 1, 1, 2−tetrafluoroethane (R134a) or 1, 1−difluoroethane (R152a) or trans−1−chloro−3, 3, 3−trifluoropropene (R1233zd(E)) or 2−chloro−3, 3, 3−trifluoropropene (R1233xf). (August 2022) - Abbadi, Jamal El; Coquelet, Christophe; Valtz, Alain; Houriez, Céline
Highlights: New VLE data for HFC/HFO with R1234yf. VLE data measured by means of static synthetic method. VLE data correlated with Peng Robinson EoS. Azeotropic behaviour for R1234yf + R134a and R152a are observed. Abstract: Isothermal vapour−liquid equilibrium (VLE) for four binary systems involving R1234yf (R1234yf + R134a, R1234yf + R152a, R1234yf + R1233zd(E) and R1234yf + R1233xf) were measured at temperatures from 278.15 to 348.15 K. The experiments were conducted by means of a "static−analytic" apparatus with phase analysis via gas chromatography, with resulting uncertainties of 0.6 K for temperature, 8 kPa for pressure and a maximum of 0.007 for vapour and liquid mole fractions. The main advantage of the equipment is that vapour and liquid samples are taken from vapour and liquid phases by two capillary samplers (ROLSI®). The Peng Robinson Equation of State is considered to represent the experimental data. If possible, comparison between the new experimental data and prediction with REFPROP 10.0 software are realized.